Demographic Process of Population Ageing in Nepal (Patan Pragya, 2021)
Population ageing is known as gradual increase in the proportion of the elderly population aged 60 years and above in the total population. In demographic process this study attempts to examine how demographic indicators i.e fertility and mortality explain the process of population ageing by subnational level in Nepal. In addition, the study also tries to assess the ageing parameters such as index of ageing, old age dependency ratio, and median age after 20 years to examine the speed of ageing process in population. This study follows descriptive and exploratory research design based on the existing data sheet of National Population Census, 2001 & 2011 and also uses other previous censuses' data collected by CBS to explore the trends in these demographic indicators and parameters. Based on almost all these indicators, this study suggests that Nepal is already in the process of population ageing. Fertility and mortality are declining with increasing in life expectancy. The growth rate of the old aged population is higher than the national population growth rate by over three-fold. Similarly, almost all the parameters of ageing seem gradually increasing over the year, which makes the conformation that greater proportion of elderly individuals in the population. This trend seems in all over the sub regions of the country but in different manner. As compared with other pace in process of population ageing is higher in Hill region and, province 3. At last study conclude population ageing is driven with the transition of the fertility and mortality where the level of fertility and mortality seems low with high life expectancy the proportion of aged population is higher and vice versa.